Implementation of Islamic Boarding School-Based Madrasah Management in Improving Student Services and Development - Muhammad Fathul Ihsan; Umi Nadhirotul Muflihah; Siti Aimah (Business and Applied Management Journal, 2025)
This research is motivated by the rapid development of science and technology in the current era of modernization which has a great influence on various areas of community life, especially in the fields of education, social, and culture, including in Islamic boarding school education. With a focus on knowing the implementation of Islamic boarding school-based madrasah management and to find out the development of students. This study uses a descriptive qualitative research method. The data collection techniques are interview, observation and documentation methods. The results of this study indicate that the Implementation of Islamic Boarding School-Based Madrasah Management that is applied has an impact on the activities of students at Ma'had whose concept is directed to carry out activities related to Islamic boarding school education and curriculum, the development given to students is given with various methods, namely through approaches and motivation, accompanied by three development indicators, namely, attendance level, ability and encouragement.